Knowledge and attitudes towards emergency contraceptive pills among university students: A cross- sectional study - Shah, Poonam; Kumar Kapar, Vijay; Chaudharee, Sabita; Prasad Chaudhary, Roshan; Chaudhary, Jyoti (Journal of Chitwan Medical College, 2025)
Introduction: Emergency contraceptive pills is to prevent the pregnancy after unprotected sexual intercourse. It helps to reduce the unwanted pregnancy and unsafe abortion. Despite of the availability of a range of modern and effective contraceptives, unwanted and unplanned pregnancies continue to occur among the adolescents. Method: A cross-sectional study was carried out to determine the knowledge and attitude of students of Rajarshi Janak University regarding the Emergency Contraceptive Pills (ECP) in Mar 2025. Data were collected using a pre-tested, structured, self-administered questionnaire. Knowledge and attitude scores were calculated, and associations with socio-demographic variables were analyzed using descriptive statistics and the Chi-square test, with a significance level of p < 0.05. Result: Out of 200 total sample, females were 107(53.5). Only 86 (43.0) of the respondents had an adequate level of knowledge about ECPs. The mean knowledge score was 3.7±1.77 (out of a possible 8). In contrast, 109(54.5) of respondents held a positive attitude towards ECPs. Adequate knowledge was significantly associated with marital status, academic program, and faculty (p<0.05). Conclusion: Student attitudes towards ECPs were generally positive, but knowledge levels were inadequate. We recommend targeted educational interventions and the integration of ECP information into the university curriculum to improve reproductive health outcomes.